America's Rise in Human Capital Mobility - Lukas Althoff; Harriet Brookes Gray; Hugo Reichardt (CESifo GmbH, 2025)
How did the US become a land of opportunity? We show that the country's pioneering role in mass education was key. Unlike previous research, which has focused on father-son income correlations, we incorporate both parents in a new measure of intergenerational mobility that considers multiple inputs, including mothers' and fathers' human capital. To estimate mobility despite limitations in historical data, we introduce a latent variable method and construct a representative linked panel that includes women. Our findings reveal that human capital mobility rose sharply from 1850 to 1950, driven by a declining reliance on maternal human capital, which had been most predictive of child outcomes before widespread schooling. Broadening schooling weakened this reliance on mothers, raising mobility in both human capital and income over time.
Keywords: 330; intergenerational mobility; human capital; economic history